2001
DOI: 10.1037/10398-000
|View full text |Cite
|
Sign up to set email alerts
|

The nature of executive leadership: A conceptual and empirical analysis of success.

Abstract: What makes for success at the highest levels of executive leadership? Until recently, most research has been conducted with middle-level managers, whose success is based on distinctively diiferent attributes those at the top.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
251
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(272 citation statements)
references
References 320 publications
5
251
1
8
Order By: Relevance
“…In this line of thought, the social intelligence competency may result in efficacy and/or high performance because the cognitive intelligence competency allows the individual to think and analyze information and also those situations that result in efficacy or high performance. Zaccaro (2001) corroborates that social intelligence is associated with effective leadership.…”
Section: Sustainability Through Leadership Self-efficacysupporting
confidence: 62%
See 1 more Smart Citation
“…In this line of thought, the social intelligence competency may result in efficacy and/or high performance because the cognitive intelligence competency allows the individual to think and analyze information and also those situations that result in efficacy or high performance. Zaccaro (2001) corroborates that social intelligence is associated with effective leadership.…”
Section: Sustainability Through Leadership Self-efficacysupporting
confidence: 62%
“…In turn, social intelligence is associated with effective leadership, according to Zaccaro (2001). However, the results obtained seem to indicate that the average scores for these attributes are lower compared to the Solving Problems attributes that reveal higher average results.…”
Section: Analysis and Discussion Of Resultscontrasting
confidence: 45%
“…They also defined the "skeptics" school, which treats leadership as a social construction (Eden & Leviatan, 1975;Meindl, Ehrlich, & Dukerich, 1985), though they have suggested that this school is mostly subsumed in the information processing perspective. Finally, they have also identified hybrid approaches as a new trend that uses a combination of the above, focuses on process perspectives, and/or does not offer a dominant theory (Lim & Ployhart, 2004;Zaccaro, 2001). …”
Section: Mode Of Inquirymentioning
confidence: 99%
“…(Dutta and Mia 2011) Integrated and multisectoral actions 1) Innovation 2) Cooperation 3) Networking 4) Area-based local development strategies 5) Bottom-up elaboration and implementation of strategies 6) Local public-private partnerships In the past, psychologists have defined leadership as a specific quality of character, talent, or skill that is innate to an individual. Still, despite this broad definition, leadership continues to be a strong area of development and research, and the scope and understanding of the concept remain unclear (Zaccaro 2001).…”
Section: Leaders and Leadership In Rural Developmentmentioning
confidence: 99%